An Anderson-type polyoxometalate triggers aerobic oxidation of 5-hydroxymethylfurfural to 2, 5-diformylfuran. (1st May 2022) - Sun, Yanbin; Zheng, Jianfeng; Xu, Jiajia; Yang, Kaixuan; Zhu, Zhiguo; Su, Ting; Ge, Hui; Ren, Wanzhong; Lü, Hongying
Highlights: Anderson-type POM catalysts with Mo 5+ -□ species were prepared successfully. A superior DFF yield (>99%) was obtained with optimal reaction condition. Mo 5+ -□ species play the key role for oxygen activation and the oxidation of HMF. The relationship between structure and DFF yield was established. Abstract: Aerobic oxidation of biomass-derived 5-hydroxymethylfurfural (HMF) to 2, 5-diformylfuran (DFF) is an environmentally sustainable, economically feasible, but substantially challenging conversion owing to the high energy barrier of O2 activation. Herein, we report a catalyst with Mo 5+ connected to the oxygen vacancies (Mo 5+ -□) in Anderson-type polyoxometalate (POM) [(C18 H37 )2 N(CH3 )2 ]6 Mo7 O24 for oxidizing HMF to DFF. The resultant catalyst with high Mo 5+ content presents superior HMF oxidation performance, delivering a > 99% DFF selectivity with complete HMF conversion. Mechanistic studies and density functional theory (DFT) calculations reveal that the Mo 5+ -□ species in the catalyst facilitate O2 activation and HMF oxidation. Moreover, the catalyst exhibits outstanding catalytic stability during the aerobic oxidation of HMF to DFF.